Regulamentação do direito à consulta prévia: análise de experiências na América Latina - LOURENÇO, João de Sousa (Universidade Federal do Oeste do Pará, 2024)
Convention No. 169/ILO represents a significant advance in the recognition of the self-determination of traditional people, through a treaty that binds the signatory States to respect the plurality of culture in their territories. As a cornerstone of the Convention, the Right to Prior, Free and Informed Consultation settles that States must consult traditional people before taking any action that could affect them. However, the States constantly disrespect that right, under allegiance of absence of clear procedures to the Public Administration. As a possible solution, there is a debate about the regulation of the right to prior consultation, as a means of making the right effective. Considering the socio-political and economic interests involved, these regulatory processes become extremely sensitive, as regulation gives States the opportunity to restrict rights already guaranteed by the international treaty, resulting in harm to traditional people. In this context, this research sought to analyze the experiences of previous consultation carried out in Peru and Chile, as well as the initiatives carried out in Brazil and within the State of Pará. Thus, it sought to identify the main vices found and to organize what would be the minimum parameters necessary for that the regulation actually contributes to the realization of the right to prior consultation. Therefore, the work was based on a literature review, with a preference for authors linked to Peruvian and Chilean universities, in order to privilege the knowledge produced by researchers close to the sociopolitical context in which the regulatory processes were developed in the respective countries, and for Brazilian authors, for the study of the processes developed in Brazil and Pará. As a result, we observed that the regulation of the right to consultation is often proposed by States as a way of distorting and restricting the terms of Convention No. 169/ILO, in order to enable greater advancement of economic sectors over natural resources. However, recognizing this sociopolitical fact is not a factor that ends discussions on the possibility of a regulation that can be beneficial to traditional peoples, as long as regulators observe minimum parameters and standards for its elaboration.